2002
DOI: 10.5650/jos.51.643
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Studies on the Optical Resolution of 2-Alkanol by Pseudomonas cepaciaLipase Catalyzed Transesterification with Vinyl Acetate in Organic Solvent.

Abstract: Vinyl acetate (VA) is a potential and practical acetylating reagent for the optical resolution of enantiomers in the racemate by lipase (triacylglycerol hydrolase, EC 3.1.1.3) catalyzed transesterification in organic solvent: VA irreversibly reacts with the active serine (Ser) residue in lipase to give the acetyl-enzyme intermediate [Enz-Ac] because vinyl alcohol is immediately converted to acetaldehyde by keto-enol tautomerization. This irreversibility is considered to accelerate the reaction rate. Such a rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 15 publications
(22 reference statements)
5
14
0
Order By: Relevance
“…The E value sharply decreased with c in the range of above 0.55 (Fig. 1B) in PCL-catalyzed transesterification between VA and 2-alkanol in various organic solvents (14). In contrast, we observed that the optical resolution data fit Eq.…”
Section: Quantitative Analyses Of Optical Resolution Datamentioning
confidence: 76%
See 4 more Smart Citations
“…The E value sharply decreased with c in the range of above 0.55 (Fig. 1B) in PCL-catalyzed transesterification between VA and 2-alkanol in various organic solvents (14). In contrast, we observed that the optical resolution data fit Eq.…”
Section: Quantitative Analyses Of Optical Resolution Datamentioning
confidence: 76%
“…Table 4 shows that 1,2-dichloroethane, acetonitrile and acetone gave higher E than the other solvents. A similsr tendency has been reported in PCL-catalyzed transesterification between TB and secondary alcohol (18)(19)(20)(21) and also in the reaction between VA and 2-alkanol (14). Thus, we selected 1,2-dichloroethane and acetonitrile as the reaction solvents and also used hexane as a standard solvent in the following studies.…”
Section: Results and Discussion 1 Solvent Screeningmentioning
confidence: 95%
See 3 more Smart Citations